Assessing the utilization of naturalized alien plant species by community to inform its management strategy: A case study in Cibodas Biosphere Reserve, West Java, Indonesia - Aisyah Handayani; Ervizal A. M. Zuhud; Decky Indrawan Junaedi (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Handayani A, Zuhud EAM, Junaedi DI. 2021. Assessing the utilization of naturalized alien plant species by community to inform its management strategy: A case study in Cibodas Biosphere Reserve, West Java, Indonesia. Biodiversitas 22: 2579-2588. Alien plant species can have two side effects, either positively in terms of the utilization of these species to fulfill human needs, or negatively in terms of their invasion which might threaten biodiversity and reduce land productivity. Yet, it is not clear how an introduced plant species can be carefully managed and utilized (so-called Naturalized Alien Plant Species/NAPS) so that the NAPS does not become Invasive Alien Plant Species (IAPS). Using Cibodas Biosphere Reserves (CBR), West Java, Indonesia as a case study, this study aims to investigate the utilization of Naturalized Alien Plant Species (NAPS) by local communities in the buffer zone of CBR and quantify the utilization of NAPS based on cultural perspective using Index Cultural Significance (ICS) framework. Data were collected by distributing questionnaires and interviewing 90 respondents in three locations around CBR: Bodogol, Cibodas, and Gekbrong. The results showed that the community used 72 Naturalized Alien Plant Species, with 30% of the utilized plants were from Asteraceae family. Centella asiatica was the most widely used species, but the species with the highest Index Cultural Significance value was Artemisia vulgaris. Based on the ICS classification, there were ten species (13.89%) with high significance values, 17 species (23.61%) with moderate significance, 30 species (41.67%) with low significance, and 15 species (20.83%) with very low significance. Species with high significance values were Artemisia vulgaris, Chimonobambusa quadrangularis, Bidens pilosa, Mentha arvensis, Amaranthus spinosus, Centella asiatica, Cyphomandra betacea, Calliandra calothyrsus, Fragaria vesca, and Solanum torvum. Based on these results, the recommended strategy is to regularly harvest the Naturalized Alien Plant Species with high ICS value to control their population and fulfill community needs.